(untitled) (Third Sector Social Economic Review, 2026)
Leisure consumption is a process through which individuals spend their time outside of work and other obligatory activities by engaging in various activities. In this process, individuals participate not only in activities aimed at rest and relaxation but also in those that provide cultural experiences. One of these activities is the local cuisine experience. This study aims to examine the interests and attitudes of individuals living in Van and originating from different geographical regions toward local cuisine experiences within the context of leisure consumption. A quantitative research approach was adopted, and data were collected through a questionnaire. The data obtained from 460 participants were analyzed using the SPSS software package. Frequency analysis, factor analysis, independent samples t-test, one-way analysis of variance (ANOVA), and correlation analysis were employed in the data analysis process. The findings revealed that participants showed interest in local cuisine experiences in addition to social, cultural, and sporting activities while spending their leisure time. The majority of participants considered Van’s local cuisine to be delicious and expressed positive attitudes toward experiencing it. Furthermore, the healthy characteristics of local dishes and their traditional presentation styles were regarded as important, and participants stated that local cuisine experiences contributed positively to their leisure time. The study is expected to contribute to a better understanding of the relationship between local cuisine and leisure consumption and to provide regional evidence for the literature on Van cuisine.